Accuracy of pre-operative parameters in predicting severe cholecystitis-A systematic review. Issue 4 (August 2021) - Khan, Sualeh Muslim; Emile, Sameh Hany; Barsom, Samer Hani; Naqvi, Syed Arsalan Ahmed; khan, Muhammad Sami
Abstract: Introduction: Severity of cholecystitis can be defined by the presence of histopathological changes such as gangrene, perforation, and empyema. Severe cholecystitis correlates with higher morbidity and longer hospital stay. The present review aimed to identify the predictors of severe cholecystitis. Methods: Electronic databases including PubMed, Scopus, and Cochrane library were searched in the period of January 1980 to March 2019. The main outcome of this review was to assess the predictability of pre-operative parameters such as Leukocytosis, fever, tachycardia, gallbladder wall edema, gallbladder distension, serum platelet count, and gallbladder mural striation. The role of patients' characteristics including age, gender, and diabetes mellitus in predicting severe cholecystitis was also assessed. Results: A total of 8823 patients were analysed. The mean age of patients was 67.14 ± 4.17. The parameters that had the highest Odds ratio in predicting severe cholecystitis were all findings on CT scanning and included attenuation of arterial phase, mural striation of the gallbladder, and decreased gallbladder wall enhancement. Conclusion: We conclude that CT findings were the most significant predictors of severe cholecystitis. Patients with clinical and laboratory predictors of severe cholecystitis should be urgently evaluated with contrast CT scan to rule out any severe complications Highlights: - Identification of severe cholecystitis can help plan treatment accordingly - CT scan has good accuracy in predicting severe cholecystitis. - Patients at high risk of severe cholecystitis should be evaluated by CT scan.